Do campo para o campus: trajetória da educação do campo no baixo Tocantins - SILVA, Benedita das Graças Sardinha da (Universidade Federal do Pará, 2020)
This article is about the study of public policy for rural education implemented at the Federal University of Pará/University Campus Abaetetuba, aiming to discuss how such policies were implemented and what the impact of these within the institution. In the research process, chose a qualitative approach, using as a methodology the literature, and as a source of data collection official documents that have public policy for rural education in Brazil. It was found from the study that these initiatives have contributed to the strengthening of research groups on campus; narrowed relations between the institution and the social movements, and raised the concern of university teacher training to work in schools field